A Real-time Data Synchronization Approach for High-availability Micro Applications - Moraes, Fernando R. de; Almeida, Daniel de; Affonso, Frank J. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
The Microservice Architecture (MSA) and the Micro Frontend Architecture (MFA) are scalable, flexible, and innovative architectures for developing micro applications (MApps). The integration of these architectures optimizes development by leveraging the strengths of both architectural styles, enabling decoupled deployment, specialized domain teams, isolated failures, scalability, and software maintenance. To the best of our knowledge, the engineering of applications based on MFA poses significant challenges, as practitioners encounter difficulties because of the dependency generated between MApps. This dependency arises from the data sharing between microservice-based applications. In a real-world execution scenario, such applications require substantial data volumes and distributed databases across microservices. While the microservices are designed to communicate via a network using lightweight communication protocols, the data interchange is relatively slow compared to the database communication. Based on the presented context, this paper proposes a real-time data synchronization approach to address the limitations of MApps development concerning communication and data replication. In order to evaluate the applicability, strengths, and weaknesses of the proposed approach, a proof of concept was conducted for a condominium management system. As a result, the evidence gathered in this paper enables us to create a favorable perspective to contribute efficiently to the MApps domain by providing an approach to this research area and an empirical evaluation for researchers and practitioners.